Considerations about the physical rehabilitation and physiotherapy on kinesiologic and functional alterations in a case of Endemic Pemphigus foliaceus - doi:10.5020/18061230.2007.p124 - Carlos Hermano da Justa Pinheiro; Wilson Martins de Sousa Filho; Denise Gonçalves Moura Pinheiro; Ana Cristhina de Oliveira Brasil (Universidade de Fortaleza, 2012)
The pemphigus foliaceus is a very common skin disease in the Center-West region of Brazil and is named endemic due to its incidence in some regions of the country, South America and Latin America. In Northeast Brazil, the pemphigus foliaceus is considered a rare disease. The bearers of endemic pemphigus foliaceus show an intense healing process associated with metabolic alterations that affect the skeletal muscle and can compromise in different ways the kinesiology of the locomotor apparatus. The aim of this study was to describe a pemphigus foliaceus case in Ceara state, focusing on the postural and functional aspects of the locomotor apparatus in the clinical evolution of the disease. Case report: A pediatric patient bearer of endemic pemphigus foliaceus, resident at a mountain region of Ceará, with clinical data consisting of erythematous lesions, crusts, few visible vesicle-blister lesions, intense itch, cutaneous adhesions, postural deformities and alterations in the flexor tonus of the limbs, compromising movement extent. The physiotherapeutic protocol prescribed consisted of active exercises, inhibition of flexor tonus, passive elongation and walk training. After 3 weeks, the patient was already strolling and showed improvement in muscular and joint function. The physiotherapy when precociously done can prevent the formation of cutaneous adhesions and muscular weakness, preserving the range of motion present in diseases with an intense healing process such as endemic pemphigus foliaceus.